Hemostatic effect of hot saline irrigation during functional endoscopic sinus surgery: a randomized controlled trial. Issue 11 (18th August 2014) - Gan, Eng Cern; Alsaleh, Saad; Manji, Jamil; Habib, Al‐Rahim R.; Amanian, Ameen; Javer, Amin R.
<x xml:space="preserve">Abstract</x> Background The endoscopically magnified operative field in functional endoscopic sinus surgery (FESS) makes even a small amount of bleeding a potentially significant hindrance. It is thought that irrigation with hot saline during surgery may improve surgical field of view by producing a hemostatic effect. Our objective was to assess the effectiveness of hot saline irrigation (HSI) compared to room temperature saline irrigation (RTSI) in the control of intraoperative bleeding during FESS. Methods Sixty‐two chronic rhinosinusitis (CRS) patients undergoing FESS were randomized to 2 treatment arms in an equal ratio. Subjects received either HSI (49°C) or RTSI (18°C), 20 mL every 10 minutes, for the duration of FESS. The Boezaart endoscopic field of view grading system was the primary outcome measure. Boezaart score, heart rate, and mean arterial blood pressure (MABP) were recorded at 10‐minute intervals between irrigations. Results Mean endoscopic surgical field of view (Boezaart score) did not significantly differ between the HSI and RTSI groups (1.5 ± 0.6 vs 1.3 ± 0.5; p = 0.23). However, when FESS was longer than 2 hours in duration, the Boezaart scores were significantly better in the HSI group (1.6 ± 0.6 vs 1.2 ± 0.4; p = 0.04). We found that blood loss per minute was significantly reduced (p = 0.02) in all cases in which HSI was used (2.3 ± 1.0) compared to RTSI (1.7 ± 1.1). Despite this, heart rate (p = 0.32) and MABP (p = 0.14) did not significantly differ between treatment groups. Conclusion HSI may be beneficial in improving surgical field of view in FESS after 2 hours of operating time. A significant reduction in rate of blood loss may be attained with HSI.